Summary of the applications of 5G and industrial internet - Qingmin YU; Ying HUANG; Weiguo WANG; Qian ZHANG (Dianxin kexue)
As an important direction for the evolution and upgrading of the information and communication industry, 5G has the characteristics of low delay, high reliability and large bandwidth, which closely match the high reliability and low delay requirements of the industrial internet.5G and industrial internet have accelerated the integration, innovation and development, and the industry has carried out multi-dimensional research and practice.Focusing on the five key industries in the development of “5G + industrial internet”, the current development status of “5G + industrial internet” was analyzed from the dimensions of policy, market, technology, products and application.